Active disturbance rejection attitude control for a hypersonic reentry vehicle with actuator saturation - Hongjiu Yang; Yang Yu; Fang Wang; Kunfeng Lu (International Journal of Advanced Robotic Systems, 2017)
In this article, nonlinear uncertainty has been investigated for a hypersonic reentry vehicle subject to actuator saturation via active disturbance rejection control technology. A nonlinear extended state observer is designed to estimate “total disturbances,” which is compensated with a linear controller. Both convergence of the nonlinear extended state observer and stabilization of the closed-loop system are studied in this article. Some simulation results are given to illustrate the effectiveness of the proposed method.